Spontaneous and superfluid chiral edge states in exciton-polariton condensates - Sigurdsson, H. (2018)
We present a scheme of interaction-induced topological band structures based on the spin anisotropy of exciton-polaritons in semiconductor microcavities. We predict theoretically that this scheme allows the engineering of topological gaps, without requiring a magnetic field or strong spin-orbit interaction (transverse electric-transverse magnetic splitting). Under nonresonant pumping we find that an initially topologically trivial system undergoes a topological transition upon the spontaneous breaking of phase symmetry associated with polariton condensation. Under either nonresonant or resonant coherent pumping we find that it is also possible to engineer a topological dispersion that is linear in wave vector—a property associated with polariton superfluidity.